2017
DOI: 10.1175/wcas-d-16-0008.1
|View full text |Cite
|
Sign up to set email alerts
|

Developing Evaluation Indicators to Improve the Process of Coproducing Usable Climate Science

Abstract: Resource managers and decision-makers are increasingly tasked with integrating climate change science into their decisions about resource management and policy development. This often requires climate scientists, resource managers, and decision-makers to work collaboratively throughout the research processes, an approach to knowledge development that is often called ''coproduction of knowledge.'' The goal of this paper is to synthesize the social science theory of coproduction of knowledge, the metrics current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
146
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(165 citation statements)
references
References 50 publications
0
146
0
Order By: Relevance
“…Arnott et al (2016) describe different purposes of evaluation, which are either to decide about the existence or funding of a program or to improve their efficiency. Most recently, Wall et al (2017) has conducted a broad review of corresponding literature and synthesize the metrics currently used to evaluate usable or actionable climate science. It is suggested that six different components should be evaluated.…”
Section: Meinke: On the Comparability Of Knowledge Transfer Activimentioning
confidence: 99%
“…Arnott et al (2016) describe different purposes of evaluation, which are either to decide about the existence or funding of a program or to improve their efficiency. Most recently, Wall et al (2017) has conducted a broad review of corresponding literature and synthesize the metrics currently used to evaluate usable or actionable climate science. It is suggested that six different components should be evaluated.…”
Section: Meinke: On the Comparability Of Knowledge Transfer Activimentioning
confidence: 99%
“…Indicators in this sense refer to a unit to asses a specific state of something. Wall et al (2017) mix up what Figure 2. The process of co-creation (on the left) spreads up into three consecutive phases (Pohl and Hirsch Hadorn, 2007), each of them can be evaluated.…”
Section: Evaluation Cascadementioning
confidence: 88%
“…The few publications dealing with criteria in a concrete manner show an enormous pool (i.e. Bergmann et al, 2005;Wall et al, 2017). Nevertheless, it seems important to compile all of the ideas in one overall representation.…”
Section: Evaluation Cascadementioning
confidence: 99%
See 2 more Smart Citations